Fluorescence Regulation and Photoresponsivity in AIEE Supramolecular Gels Based on a Cyanostilbene Modified Benzene‐1, 3, 5‐Tricarboxamide Derivative1. Issue 1 (4th December 2018) - Ding, Zeyang; Ma, Yao; Shang, Hongxing; Zhang, Houyu; Jiang, Shimei
Abstract: Supramolecular interactions play an important role in regulating the optical properties of molecular materials. Different arrangements of identical molecules can afford a more straightforward insight into the contributions of supramolecular interactions. Herein, a novel gelator, BTTPA, composed of a benzene‐1, 3, 5‐tricarboxamide (BTA) central unit functionalized with three cyanostilbenes is designed, which forms two kinds of gels in DMSO/water mixtures. Depending on the water volume content, the gels exhibit quite different aggregation‐induced emission enhancement (AIEE) properties, with one emitting a green emission (G‐gel), and the second emitting a blue emission (B‐gel). The main reason for this difference is that water affects H‐bonding and π–π interactions, further resulting in disparate packing modes of gelators. In addition, only the G‐gel displays gel‐to‐sol transition accompanied with fluorescence switching according to the trans‐cis photoisomerization of cyanostilbene under UV light irradiation. The B‐gel does not exhibit any change because of its tight hexagonal packing arrangement. Such packing modes restricted the space in which molecules were located and inhibited the transformation of configuration of cyanostilbene. These phenomena underline the incomparable status of packing modes and molecular configuration in regulating fluorescence properties and photoresponse behavior in organic solid‐state luminescent materials. Abstract : All in order : Modulation of fluorescence properties can be achieved at the unimolecular level by controlling ordered molecular self‐assemblies. Herein, a novel gelator, BTTPA, is shown to form two kinds of gels with one emitting a green emission (G‐gel), and the other emitting a blue emission (B‐gel), depending on the water content in DMSO/water mixtures (see figure). Only the G‐gel displays high photosensitivity; the B‐gel does not exhibit any change upon UV irradiation.